LA MAIN PASSIVE: ABSENCE D’ŒUVRE, RESISTANCE ET DESŒUVREMENT - Patricia APOSTOL (Studia Universitatis Babeș-Bolyai. Philosophia, 2018)
The Passive Hand: Absence d’œuvre, Resistance and Désœuvrement. I question the rapport between the hand as an aesthetic notion and the value of passivity, in order to define the dynamic of the relationship between passivity and creation. I, first, examine the Blanchot’s metaphor regarding the act of creation as being a privative intervention of the left hand, passive, on the right hand, active, under the light of a critical reading of the Nietzschean concepts of active force—reactive force; then, I analyse the passivity of the discourse under three types of rapport: the inspiration and the absence of the œuvre, the resistance and the œuvre, the disobedience and the désœuvrement. From the absence of the œuvre of the inspired artist to the resistance at the œuvre, which creates the œuvre, and lastly, to the reactive force which affirms the refusal of the œuvre and produces the absence of the œuvre, passivity makes a circular movement from the impossibility of the oeuvre towards the désœuvrement, from from its genesis to its heterogenesis.